Bilateral ureterocele diagnosed late in a 36-year-old woman, complicated by a right ureterocele stone: A case treated endoscopically - Clotaire Alexis Marie Kiemdiba Donega Yaméogo; Brahima Kirakoya; Hassami Sawadogo; Klovis Klifford Kaboré; Ouinlassida Robert Zoungrana; Adama Ouattara; Fasnéwindé Aristide Kaboré (Urology Case Reports)
We report the case of a 36-year-old woman presenting with chronic bilateral flank pain and lower urinary tract symptoms. A CT urography revealed bilateral intravesical ureteroceles with a stone impacted in the right ureterocele, causing grade 3 hydronephrosis. Management consisted of bilateral semicircular ureterocele incisions, Holmium laser vaporization of the impacted stone, and bilateral JJ stent placement. The postoperative course was uneventful, with symptom resolution and normalization of the urinary tract anatomy.